Optimized Conditions of Acid Digestion Procedure for Metals Determination in PM2.5 Samples by ICP-OES - Thepnuan, Duangduean; Phromsenjai, Phichit; Krasitnitikul, Pavidarin; Insian, Wittawat (Burapha Science Journal, 2024)
Background and Objectives : The limitations of chemical analysis in particulate samples for air pollution monitoring are limited sample amount and detection limits of some critical parameters, such as trace metals with low concentrations in the nanogram per milliliter level. This research aims to optimized conditions of acid digestion of particulate matter samples for trace metal determination by using inductively coupled plasma optical emission spectroscopy (ICP-OES). Methodology : PM2.5 samples were collected during the Yi Peng Festival in 2019 with a high-volume air sampler, at a flow rate of 1000 liters per minute for 24 hours. A total of 7 samples with different concentrations of trace metals were used for optimization study for 5 methods of acid digestion conditions. Different parameters such as sample amount, type and amount of acid, heating methods were selected to obtain the best performance. The method validation was then evaluated for the determination of 11 types of metals, including Ca, Mg, K, Fe, Mn, Zn, Cu, Cr, Cd, Pb and Ni in PM2.5 samples by ICP-OES technique. Main Results : The most suitable digestion method was found to be as follows : degesting 1 piece of PM2.5 samples with diameter 4.71 centimeter using a mixture of 16.75% hydrochloric acid and 5.55% nitric acid in a volume of 20 milliliters, heating the samples with a test tube heater at 95 degrees Celsius and adjusting to a final volume of 10 milliliters before the measurement. The validation of the analysis for 11 metals showed that the linearity range was between 0.001-10 ppm, with the correlation coefficients (r2) ranging from 0.9981 to 0.9998. The limits of detection (LOD) ranged from 0.015 to 0.154 ppm, and the limits of quantification (LOQ) ranged from 0.031 to 0.323 ppm. The accuracy in terms of percentage recovery (%Recovery) ranged from 80-120%. The precision in terms of relative standard deviation (%RSD) ranged from 2-7%, except for Ca, K, Mg, and Pb. Conclusions : The optimized conditions of acid digestion can significantly enhance the ability of trace metal determinations in PM2.5 samples by ICP-OES. The method of metal analysis presented in this work would be useful for atmospheric chemistry research, particularly in assessing the sources of pollutants and their health impacts.